Relationship Between Managerial Support and Hospital Atmosphere With Burnout Among Nurses at COVID-19 unit - Nurul Khosnul Qotimah; Mira Triharini; Andri Setiya Wahyudi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2021)
Introduction: Hospital atmosphere and managerial support during the COVID-19 pandemic are important factors in determining the quality of nursing care, however, support that is not provided properly can cause work stress, causing burnout syndrome which results in low quality of work. The purpose of this study was to explain the relationship between managerial support and hospital atmosphere with burnout syndrome of nurses at COVID-19 unit. Methods: The research design was correlational descriptive with a cross-sectional approach. A total of 64 nurses at COVID-19 unit at the referral hospital for COVID-19 patients in Surabaya who handle COVID-19 patients directly for at least 2 months and treat COVID-19 patients at least 1-2 patients every day in the isolation room were selected through a simple random sampling method. The variables in this study were managerial support, hospital atmosphere, and burnout syndrome. Perceived managerial support was measured by the Managerial Support Questionnaire, the Hospital Atmosphere Questionnaire for perceived hospital atmosphere, and the Maslach Burnout Inventory to measure burnout syndrome. The results were analyzed by descriptive analysis and logistic regression test with a significance value of p≤ 0.05. Results: The results showed that there was a significant relationship between managerial support (p = 0.027) and hospital atmosphere (p = 0.026) with burnout syndrome. The relationship between managerial support and hospital atmosphere is negative. The higher the managerial support and hospital atmosphere, the lower the burnout syndrome level. Conclusion: High managerial support and a good hospital atmosphere can reduce burnout syndrome among nurses at COVID-19 unit. The results of this study are expected to be a reference for hospitals in preventing nurse burnout syndrome so that the quality of service increases.